Maringá de todos os santos: presença das religiões afro-brasileiras - Silva, Eronildo José da (2014)
The study Maringá of all saints: presence of Afro-Brazilian religions seeks, from the observation of the denial of the black presence in Maringá, to reveal that presence, hidden as it is in its religious expressions. The Afro-Brazilian religious universe in Maringá is, still today, little known by most people. Our interest, in this study, is to reveal it through the shrines active in the city, their origins, filiations (lineage), their priests and followers, how they face prejudice that is, in fact, still very strong, and the relations between shrine groups and society. Revealing the presence of those religions, the study seeks to contribute not only to the knowledge of the origins and path of the Afro-Brazilian religions in Maringá, but also of their capability of resistance and affirmation in a notoriously adverse religious scene